The Analysis of MSMEs Financial Statements Preparation Based on SAK-EMKM to Develop the MSMEs Financial Performance - Dunakhir, Samirah (PINISI Discretion Review, 2023)
The urgency of this research begins with the results of previous research which shows that many MSMEs do not yet have an Accounting Information System that is capable of producing financial reports required by credit providers or in accordance with established rules, which is the Financial Accounting Standards (SAK) for Micro, Small and Medium Entreprise (EMKM). This results in many MSMEs not having credible and good financial reports. Therefore, the aim of this research is to analyze the preparation of MSMs Financial Reports based on SAK-EMKM in Makassar City. The research type is qualitative study. The number of MSMEs sampled in this research was 28 MSMEs. The data used in this research are primary data and secondary data. Primary data was obtained directly from the results of filling out the questionnaire, while secondary data was obtained from the financial reports of MSMEs in Makassar City. The research results show that MSMEs in the city of Makassar make financial reports in accordance with the creativity, abilities and knowledge of MSME owners. The results of the questionnaire show that MSMEs in Makassar City have not implemented SAK EMKM. This is due to the lack of knowledge of MSME owners regarding Financial Reports that based on SAK-EMKM.